Probiotics' effects on gut microbiota in jaundiced neonates: a randomized controlled trial protocol - Jiayi, Chen; Jinying, Wei; Yanhan, Yuan; Tianyu, Liu; Juanjuan, Chen; Feng, Zhang; Xiaohui, Fang; Jinping, Zhang (Frontiers in Pediatrics, 2024)
Introduction Recent evidence suggests that blue-light phototherapy impacts gut microbiota composition in jaundiced newborns, leading to disturbances closely related to the therapy's side effects. As a result, gut microbiota may serve as a potential intervention target to mitigate these side effects. In this study, we aim to examine the effects of AB-GG (Lactobacillus rhamnosus LGG), Bb-12 (Bifidobacterium animalis Bb-12) and M-16V (Bifidobacterium breve M-16V) and their combination on the intestinal microbiota, metabolomics and phototherapy-related side effects in neonates with jaundice. Methods and analysis A total of 100 jaundiced newborns aged two weeks or younger will be included in this randomized, single-blind (the parents knew, but the neonatologists did not know), single-center controlled trial to receive either 109 colony-forming units of AB-GG, Bb-12, M-16V, a combination of the three probiotics with blue-light phototherapy, or blue-light phototherapy alone. The experimental group will be treated with oral probiotics once daily for 30 days, while the control group will receive only blue-light phototherapy. The follow-up duration will last 30 days. The primary outcomes include changes in gut microbiota, metabolomics, and the incidence of phototherapy side effects, assessed after each phototherapy session, as well as on days 10, 20, and 30. Ethics and dissemination The study protocol has been approved by the Ethics Committee of our institution. The findings of this trial will be submitted to a peer-reviewed pediatric journal. Its abstracts will be submitted to relevant national and international conferences. Clinical Trial Registration http://www.chictr.org.cn/index.aspx, identifer (ChiCTR2000036013).